THE USE OF DRONE AND VISIBLE ATMOSPHERICALLY RESISTANT INDEX (VARI) ALGORITHM IMPLEMENTATION IN MANGROVE ECOSYSTEM HEALTH’S MONITORING - Sewiko, Roni; Sagala, Herlina Meria Uli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Operational limitations are the main problem in monitoring 3.31 million hectares of mangrove forest areas throughout Indonesia. However, with the disruption of technology, there are currently many approaches and methods that can be adapted to answer these problems. One of them is drone technology. This technology can be utilized in high-resolution rapid mapping for limited areas. The output from the data acquired by the drone can be analyzed for various purposes, including assessing the health condition of the vegetation. In this study, the results of the acquisition of unmanned aircraft on mangrove vegetation are used to determine the health level of vegetation in mangrove conservation areas. The research was conducted on 46 hectares of mangrove conservation area. The acquisition process was divided into four flying missions with a flight height of 150 m, 80% patching, and using the Hasselblad L1D-20c camera with a 1-inch sensor. The acquisition results are processed using the online photogrammetry method through the cloud-based photogrammetry service from DroneDeploy. Processing uses standard mode, where this mode is designed to produce good image quality with a relatively fast processing time. The acquisition results of 1614 photos were 100% successfully aligned, with 3.50 cm/px GSD resolution. Based on the application of the VARI algorithm to the resulting orthophoto, it is known that 30.2692% of the AOI is an area and/or dead or non-vegetated vegetation. Then 59.3887% is vegetation in an unhealthy condition, 10.3405% is considered as vegetation in healthy condition, and 0.0015% is vegetation in very healthy condition.